ANALISIS LAPORAN AKUNTABILITAS KINERJA PADA DINAS PARIWISATA DAN KEBUDAYAAN KABUPATEN KOLAKA TIMUR - Andriani, Indri; Chairunnas, Arnadi; Bustang, Bustang (Jurnal Akuntansi Kompetif, 2025)
Indri Andriani (181821540) Faculty of Social and Economic Sciences, Accounting Study Program. "Analysis of Performance Accountability Report at the Tourism and Culture Office of East Kolaka Regency". Guided by Mr. Arnadi Chairunnas as Supervisor I and Mr. Bustang as Supervisor II. This study aims to determine the Performance Accountability Report at the Tourism and Culture Office of East Kolaka Regency. This study uses a Qualitative research method with a descriptive approach. In collecting data, researchers use data collection techniques, namely interviews and documentation. The data analysis technique used is the Accountability Report. The results of the study indicate that the LAKIP at the Tourism and Culture Office of East Kolaka Regency has been presented but is not in accordance with the guidelines of the Regulation of the Minister of State for Empowerment of State Apparatus and Bureaucratic Reform No. 29 of 2010, where in article 16 paragraph 1 it is stated that the Performance Accountability Report as referred to in article 12 contains a summary of the achievement of targets as stipulated in the performance determination document and planning document. However, the facts found by researchers when conducting research at the Tourism and Culture Office of East Kolaka Regency, the implementation of the LAKIP presented cannot be said to be appropriate, making it difficult for the author to clearly describe the financial resources used to carry out activities in achieving outputs and results (outcomes).